2022
DOI: 10.1101/2022.08.01.22278219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The health impact of long COVID during the 2021-2022 Omicron wave in Australia: a quantitative burden of disease study

Abstract: Objectives To quantify the morbidity impact of long COVID in Australia during the 2021-2022 Omicron wave in comparison to acute COVID-19 morbidity and mortality, and to other causes of morbidity and mortality in Australia. Design Burden of disease study using inputs from previously published population-based case-control, cross-sectional, or cohort studies. Setting Australia Participants People with symptomatic COVID-19 infection from 10/12/21 to 09/04/22. Main outcomes measured Years lived with dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…The prevalence of cough in our COVID-19 patients after discharge (15%) was similar to what has been reported in other studies (19). Research has shown that vaccinated individuals and those infected with the Omicron variant have a lower risk of developing long COVID syndrome (20). This may explain why there was no difference in long COVID syndrome among our patients.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of cough in our COVID-19 patients after discharge (15%) was similar to what has been reported in other studies (19). Research has shown that vaccinated individuals and those infected with the Omicron variant have a lower risk of developing long COVID syndrome (20). This may explain why there was no difference in long COVID syndrome among our patients.…”
Section: Discussionsupporting
confidence: 90%
“…The pathogenesis of PASC has started to make sense [5], but a consensus on diagnosis appears out of reach for many who struggle with prolonged post-viral effects. It is notable that the majority of the years lived with disability due to COVID-19 appear attributable to long COVID, when only a minority of acute cases go on to develop the long form [6]. If you are still not convinced that this is a real, organic disease entity, read a patient's account and reflect on how this could easily have been you [7].…”
mentioning
confidence: 99%